2023
DOI: 10.1007/s12020-023-03337-3
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the cardio-metabolic impact of the COVID-19 pandemic

Abstract: Evidence has shown that cardiometabolic disorders (CMDs) are amongst the top contributors to COVID-19 infection morbidity and mortality. The reciprocal impact of COVID-19 infection and the most common CMDs, the risk factors for poor composite outcome among patients with one or several underlying diseases, the effect of common medical management on CMDs and their safety in the context of acute COVID-19 infection are reviewed. Later on, the changes brought by the COVID-19 pandemic quarantine on the general popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 136 publications
0
1
0
Order By: Relevance
“…18,28 Investigations carried out by the Saudi Arabian Ministry of Health have identified that conditions like diabetes, hypertension, chronic heart diseases, asthma, and chronic obstructive pulmonary disease heighten the likelihood of hospitalization and lead to extended stays in intensive care units. 29,30 Additional research has corroborated the negative consequences of pre-existing chronic illnesses on COVID-19 patients, 31 particularly noting the unfavorable prognosis for individuals with both diabetes and COVID-19. 32 The research also found that regardless of the presence of chronic conditions, there was an increase in the duration of emergency treatment and daily expenses per patient.…”
Section: Dovepressmentioning
confidence: 98%
“…18,28 Investigations carried out by the Saudi Arabian Ministry of Health have identified that conditions like diabetes, hypertension, chronic heart diseases, asthma, and chronic obstructive pulmonary disease heighten the likelihood of hospitalization and lead to extended stays in intensive care units. 29,30 Additional research has corroborated the negative consequences of pre-existing chronic illnesses on COVID-19 patients, 31 particularly noting the unfavorable prognosis for individuals with both diabetes and COVID-19. 32 The research also found that regardless of the presence of chronic conditions, there was an increase in the duration of emergency treatment and daily expenses per patient.…”
Section: Dovepressmentioning
confidence: 98%